Constructing a Mixed Methods Research Design: Exploration of an Architectural Intervention - Kong, Seng Yeap; Yaacob, Naziaty Mohd; Mohd Ariffin, Ati Rosemary (SAGE Publications, 2018)
The aim of this methodological description is to illustrate the application of mixed methods research in architectural design using a hybrid model consisting of a taxonomy development model and an embedded quasi-experimental model. The research employed qualitative and quantitative methods to explore the design of an architectural intervention and determine its effectiveness in improving environmental knowledge, attitudes, and behavior among primary school students. It also outlined strategies adopted to overcome the challenges related to the use of a hybrid design. Combining sequential and embedded mixed methods designs is a relatively new approach in architectural research, providing new insights that contribute to future mixed methods exploration in the field of design and planning.